Long-term monitoring of thinning for silvopastoral purposes in Nothofagus antarctica forests of Tierra del Fuego, Argentina - Martínez Pastur, Guillermo José; Soler Esteban, Rosina Matilde; Lencinas, María Vanessa; Cellini, Juan Manuel; Peri, Pablo Luis (Forest Systems, 2018)
Aim of the study: To analyse the effectiveness of thinning on tree growth, forest structure and microclimatic variables along seven years after cuttings in a secondary Nothofagus antarctica forest in Southern Patagonia. Area of study: Five hectares of homogeneous stand of secondary forests (54º15’46” SL, 66º59’41” WL) in Tierra del Fuego, Argentina. Material and methods: One control and two thinning levels were established, and forest structure, growth, crown dynamic and microclimate variables in long-term permanent plots were evaluated. Main comparisons were made using multiple ANOVAs. Main results: Intensive thinning in secondary forests allowed to increase tree individual growth rates by doubling the radiation levels at the understory level that enhances the silvopastoral management. These forests showed a desirable resilience to the forest interventions and natural disturbances (e.g. heavy defoliator attack), with a rapid reaction in the canopy cover growth. Research highlights: Monitoring of thinning for silvopastoral management must include easy and cheap measuring variables, e.g. diameter growth as a proxy for timber production objectives and hemispherical photos (crown cover and radiation) as a proxy for pasture production. Long-term monitoring allowed to identify reliable indicators that assist new sustainable management alternatives. EEA Santa Cruz Fil: Martínez Pastur, Guillermo José. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas. Laboratorio de Recursos Agroforestales; Argentina Fil: Soler Esteban, Rosina Matilde. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas. Laboratorio de Recursos Agroforestales; Argentina Fil: Lencinas, María Vanessa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas. Laboratorio de Recursos Agroforestales; Argentina Fil: Cellini, Juan Manuel. Universidad Nacional de La Plata. Laboratorio de Investigación de Sistemas Ecológicos; Argentina Fil: Peri, Pablo Luis. Universidad Nacional de la Patagonia Austral; Argentina. Instituto Nacional de Tecnología Agropecuaria (INTA). Estación Experimental Agropecuaria Santa Cruz; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina